Fabrication of pyrolytic carbon interdigitated microelectrodes by maskless UV photolithography with epoxy-based photoresists SU-8 and mr-DWL - Nicolai Støvring; Babak Rezaei; Arto Heiskanen; Jenny Emnéus; Stephan Sylvest Keller (Micro and Nano Engineering, 2024)
Maskless UV photolithography is increasingly used, especially in research environments where low turn-around time for new designs improves productivity. Here, we fabricate pyrolytic carbon interdigitated microelectrodes with small interelectrode gaps, good adhesion to the carrier substrate, high surface area and excellent electrochemical properties using maskless UV photolithography with two negative epoxy-based photoresists, namely the commonly used SU-8 and the recently developed mr-DWL. The minimum realizable trench width in 15 μm thick photoresist films is 2.4 ± 0.15 μm for mr-DWL 5 and 3.1 ± 0.10 μm for SU-8 2035. After pyrolysis, the two resulting pyrolytic carbon materials show similar electrochemical properties. However, shrinkage during pyrolysis is significantly lower for mr-DWL compared to SU-8, which is beneficial for the fabrication of interdigitated microelectrodes. Furthermore, delamination of the electrodes during processing and operation is prevented due to the introduction of poly silicon adhesion structures. This work provides valuable insights into maskless UV lithography as well as into the pyrolytic carbon process to increase the yield, performance and productivity for fabrication of microelectrodes.